Usage of Scholarly Electronic Journals: Transaction Log Analysis of Turkish Librarianship Journal - Çağdaş Çapkın (Türk Kütüphaneciliği)
The purpose of this study was to conduct a transactional log analysis on Turkish Librarianship (TL) journal’s web site. For this purpose, more than 165.000 visitors’ transaction data within three years (between July, 2010 and July, 2013) was obtained from Google Analytics and analyzed. The main findings showed that TL was a local journal. In addition to library and information science topics, general public and interdisciplinary topics were attracting more visitors. Visitors significantly preferred to download full-text documents rather than to display metadata.